Stress Management: Understanding Stress - Joe Pergola; Suzanna Smith (EDIS, 2003)
Stress management begins with you. Your reaction to stressors is very important. Your response impacts how stressful situations will be to your body, mind, emotions and relationships. The first step to managing stress is awareness. You have to be aware of the warning signs in your body that you are under stress. Then you can do something to stop stress. This publication is FCS2080, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. First Publication: June 1989 as FCS2081. Reviewed: August 1999. Revised: January 2003.